TSAI–TOKAD (T–T) Graph: The Combination of Non-Oriented and Oriented Graphs for the Kinematics of Articulated Gear Mechanisms - Uyguroğlu, Mustafa; Demirel, Hasan (Meccanica: An International Journal of Theoretical and Applied Mechanics, AIMETA / Springer, 2005)
ABSTRACT : The non-oriented and oriented linear graph techniques are used for the kinematic analysis of bevel-gear trains. In this paper, these two techniques are compared and the weaknesses of each technique are shown. In order to overcome the weaknesses of these techniques a new graphical technique called Tsai–Tokad (T–T) graph is introduced incorporating the important feature of the non-oriented graph which helps to determine the transfer vertex and the oriented graph technique. The theory is demonstrated by the kinematic analysis of articulated robotic mechanism used by Cincinnati Milacron T³.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1007/s11012-005-4023-8) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Geared Wrist Manipulators - Kinematic Analysis - Mechanics of Machines - Oriented and Non-Oriented Graphs; Mechanical Engineering - Mechanics